Therapeutic Potential of Cannabinoids in Glaucoma - Theresa Lindner; Doreen Schmidl; Laura Peschorn; Viktoria Pai; Alina Popa-Cherecheanu; Jacqueline Chua; Leopold Schmetterer; Gerhard Garhöfer (MDPI AG, 2023)
Glaucoma is a leading cause of irreversible blindness worldwide. To date, intraocular pressure (IOP) is the only modifiable risk factor in glaucoma treatment, but even in treated patients, the disease can progress. Cannabinoids, which have been known to lower IOP since the 1970s, have been shown to have beneficial effects in glaucoma patients beyond their IOP-lowering properties. In addition to the classical cannabinoid receptors CB1 and CB2, knowledge of non-classical cannabinoid receptors and the endocannabinoid system has increased in recent years. In particular, the CB2 receptor has been shown to mediate anti-inflammatory, anti-apoptotic, and neuroprotective properties, which may represent a promising therapeutic target for neuroprotection in glaucoma patients. Due to their vasodilatory effects, cannabinoids improve blood flow to the optic nerve head, which may suggest a vasoprotective potential and counteract the altered blood flow observed in glaucoma patients. The aim of this review was to assess the available evidence on the effects and therapeutic potential of cannabinoids in glaucoma patients. The pharmacological mechanisms underlying the effects of cannabinoids on IOP, neuroprotection, and ocular hemodynamics have been discussed.